Pregnancy outcome in women with polycystic ovary syndrome comparing the effects of laparoscopic ovarian drilling and clomiphene citrate stimulation in women pre-treated with metformin: a retrospective study - Vytiska-Binstorfer Elisabeth; Wirth Stefan; Nouri Kazem; Kurz Christine; Ott Johannes; Huber Johannes C; Mayerhofer Klaus (BMC, 2010)
Abstract Background Ovarian stimulation in women with polycystic ovary syndrome (PCOS) increases the risk for perinatal complications. Ovulation induction by laparoscopic ovarian drilling (LOD) might improve the overall pregnancy outcomes. The aim of our study was to assess the adverse events or effects on pregnancy of LOD and clomiphene citrate (CC) stimulation in patients who received metformin. Methods Setting: Academic research institution. We retrospectively analyzed the courses of 40 spontaneous pregnancies after LOD for CC-resistance, 40 pregnancies after CC stimulation, and 40 pregnancies after metformin treatment alone. Patients in the LOD and the CC groups had been pre-treated with Metformin. Primary outcome parameters were: the rate of multiple pregnancies; the rate of early pregnancy losses/miscarriages; the development of gestational diabetes, pregnancy-induced hypertension, and preeclampsia/HELLP-syndrome; premature delivery; and birth weight. Results The rate of twin pregnancies did not differ between the CC group (12.5%), the LOD group (7.5%), and the metformin only group (2.5%, p = 0.239). Seventeen women suffered an early miscarriage. There were no differences with regard to the rates of gestational diabetes, pregnancy-induced hypertension, preeclampsia, and preterm delivery. By analyzing all pregnancy complications together, the overall pregnancy complication rate was highest in the CC group (70.0%, 28/40), followed by the LOD group (45.0%, 18/40), and the metformin only group (47.5%, 19/40; p = 0.047). Conclusions CC, but not LOD, increases the complication rate in pregnant patients who received metformin.